Katekis Sebagai Pembina Kaum Muda Dalam Upaya meningkatkan Kehidupan Menggereja - Damiana ley; Intansakti Pius X (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2024)
The title of this research is Catechist as a youth coach in an effort to improve church life. A catechist is someone who is called and sent by the Church to proclaim God's work of salvation. Catechists also play a role in fostering and accompanying young people to be involved in church life. Young people are part of the Church who have the responsibility to develop their Church. This research uses a literature review method in the form of data collection through articles and documents related to the research title. The purpose of this research is to elaborate on the role of catechists as coaches of young people in the Church. The result of this study is that young people are part of the Church and they are the future of the Church, they have an important role in efforts to develop church life. But many young people are not yet actively involved in carrying out the duties of the Church. The presence of catechists will greatly help young people to accompany and move them to be involved in the Church.